Electric vehicle battery charging station based on bipolar dc power grid with grid-to-vehicle, vehicle-to-grid and vehicle-to-vehicle capabilities - Sousa, Tiago José Cunha (2023)
An electric vehicle (EV) battery charging station (EV-BCS) based on a bipolar dc power grid is presented in this paper, which is capable of delivering power to the grid (vehicle-to-grid – V2G mode), and directly exchange power between different EVs connected to the EV-BCS (vehicle-to-vehicle – V2V mode), besides the traditional battery charging operation (grid-to-vehicle – G2V mode). The presented EV-BCS is based on three-level bidirectional buck-boost dc-dc converters and has a modular structure. Simulation results are presented with the aim of validating the aforementioned operation modes, being considered two EVs for simplicity reasons, since it is enough to validate the proposed operation modes. The presented results comprise both balanced and unbalanced operation in terms of power from the EVs viewpoint, with the purpose of considering a real scenario of operation, where a balanced consumption or power injection from the bipolar dc power grid side is always guaranteed.